Serum Leptin Levels in Stable Asthmatic Patients and Relation Between Leptin and Severity of Asthma, and Obesity - Kirkil, Gamze; Deveci, Figen; Muz, M. Hamdi; Ilhan, Fulya; Cakir, Yasemin (Aves, 2006)
The incidence of asthma is increasing among obese people. It is thought that leptin may play a role in pathogenesis of obesity related asthma. We aimed to investigate the relation between serum leptin levels and obesity, and severity of asthma. Body mass index (BMI), serum leptin, THE-, IL-6 levels, and FEV1, FEV1 IFVC and PEF values of 30 stable asthmatic patients and 10 healthy controls were evaluated. There was no difference in BMI between asthmatic and control cases (p>0.05). Serum TNF-, IL-6, IL-2, leptin levels of asthmatic cases were higher than control cases (p=0.001, p=0.001, p=0.009, p=0.001 respectively). TNF-, IL 12, leptin levels of moderate persistent (MoP) (p=0.005, p=0.053, p=0.004 respectively) and severe persistent (SP) (p<0.001, p<0.001, p<0.001 respectively) asthmatic cases were higher than controls. IL-6 levels of mild persistent (MP), MoP, SP asthmatic cases were higher than controls (p=0.023, p=0.001, p=0.008 respectively). TNF-, IL-12 and leptin levels were high in SP asthmatics compared with MP asthmatics (p=0.003, p=0.006, p=0.034 respectively). BMI of MoP and SP asthmatics were higher than MP asthmatics (for MoP p=0.022, for SP p=0.001), BMI of SP asthmatics were high when compared with controls (p=0.006). In asthmatics a positive correlation between leptin levels and BMI, TNF-, IL-12 ( R00.353, p=0.025, R=0.610, p=0.001, R= 0.492, p=0.001 respectively), and a negative correlation between BMI and FEV1, FEV1 IFVC, PEF values ( R=0.654, p=0.000, R=-0.522, p<0.003, R=-0.668, p=0.000, respectively) was found. Any correlation was not found between leptin levels and FEV1, FEV! IFVC, PEF values. Results of our study suggests that a relation can be present between asthma and obesity, and leptin can take part in asthma pathogenesis especially by increasing inflammation.
Keywords: asthma; cytokine; leptin; obesity